Public service broadcasting and diversity in the digital age: policy and options for SABC television - Skinner, Katherine Alicia Mary (My University, 2017)
The thesis critically analyses the potential of digital technologies – in particular, digital terrestrial television – to enable substantive diversity of programming in a public service broadcaster, the South African Broadcasting Corporation. The thesis deploys critical political economy of the media approaches. These approaches argue for a social constructivist approach to technology and not a celebratory determinist approach, which confuses the potential of technology with what actually happens in ‘real world’, contested policy contexts. The research uses qualitative methodologies, specifically thematic analyses of policy texts and in-depth interviews with policy actors and informants. Ultimately, the thesis finds that the changing political context in South Africa, which has moved away from participatory policy making processes, has resulted in missed opportunities to harness the digital potential to diversify programming. The thesis finds that with the government’s deployment of more authoritarian ‘statist’ and market-orientated policies, the policy space has narrowed, ultimately limiting the possibilities for the delivery of substantive diversity of content and programming. Finally, the thesis finds that to begin to reverse these trends in the digital, multi-channel environment, the government needs to (re)commit to consultative policy making processes and to regulation and public funding in the public interest.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, for the degree of Doctor of Philosophy
Keywords: South African Broadcasting Corporation; Public broadcasting--South Africa; Broadcasting policy--South Africa; Television broadcasting--South Africa